Migraine and Epilepsy: Review of the Literature. Issue 3 (7th March 2015) - Nye, Barbara L.; Thadani, Vijay M.
<x xml:space="preserve">Abstract</x> Migraine and epilepsy are disorders that are common, paroxysmal, and chronic. In many ways they are clearly different diseases, yet there are some pathophysiological overlaps, and overlaps in clinical symptomatology, particularly with regard to visual and other sensory disturbances, pain, and alterations of consciousness. Epidemiological studies have revealed that the two diseases are comorbid in a number of individuals. Both are now recognized as originating from electrical disturbances in the brain, although their wider manifestations involve the recruitment of multiple pathogenic mechanisms. An initial excess of neuronal activity in migraine leads to cortical spreading depression and aura, with the subsequent recruitment of the trigeminal nucleus leading to central sensitization and pain. In epilepsy, neuronal overactivity leads to the recruitment of larger populations of neurons firing in a rhythmic manner that constitutes an epileptic seizure. Migraine aura and headaches may act as a trigger for epileptic seizures. Epilepsy is not infrequently accompanied by preictal, ictal, and postictal headaches that often have migrainous features. Genetic links are also apparent between the two disorders, and are particularly evident in the familial hemiplegic migraine syndromes where different mutations can produce either migraine, epilepsy, or both. Also, various medications are found to be effective for both migraine and epilepsy, again pointing to a commonality and overlap between the two disorders.